(untitled) (Quinto Sol, 2013)
This article focuses on the ecclesiastical revenues produced by the tithes of the diocese of Buenos Aires, its allocation within the Church, and the portion absorbed first by the Royal Treasury and by the independent governments after 1810. It analyzes ecclesiastical revenues troughtout a long period of time, from the creation of the viceroyalty of the Río de la Plata in 1776 until the abolition of the tithes in the Province of Buenos Aires in 1821. This article studies long-term variations in revenue produced by the tithes, and how different sectors within the ecclesiastical hierachy-bishops, the cathedral chapter, parsons of the cathedral and of the major parishes,etc.- and the State treasury were affected by these changes. Finally, it analyzes how the revolution of Independence and the political and military events that followed the break-up of the viceroyalty affected the collection and distribution of ecclesiastical revenues.